Various neuromodulation methods including Deep Brain Stimulation of the medial forebrain bundle combined with psychopharmacotherapy of treatment-resistant depression—Case report - Rymaszewska, Joanna; Wieczorek, Tomasz; Fila-Witecka, Karolina; Smarzewska, Katarzyna; Weiser, Artur; Piotrowski, Patryk; Tabakow, Paweł (Frontiers in Psychiatry, 2023)
Treatment-resistant depression remains one of the main concerns of modern psychiatry. Different therapeutic methods are available and more and more factors contributing to treatment resistance are being discovered. This case report presents a patient treated initially with standard pharmacotherapy and psychotherapy. Because of high symptom severity and diagnosed treatment resistance additional therapeutic approaches were introduced sequentially: Electroconvulsive Therapy (ECT), Transcranial Magnetic Stimulation (intermittent Theta Burst Stimulation, iTBS) and finally Deep Brain Stimulation (DBS) of the medial forebrain bundle. ECT was efficient for only 4 months, iTBS improved just insomnia, whereas DBS combined with pharmaco-and psychotherapy allowed to reach full remission, however during the whole observational period several difficulties and deteriorations have been met. At the end of the 20th month of active DBS a reduction of more than 80% of depressive symptom severity was observed (measured with Montgomery-Asberg Depression Rating Scale and Hamilton Depression Rating Scale), together with 87% reduction of anxiety symptoms intensity (Hamilton Anxiety Rating Scale) and 90% increase in Social and Occupational Functioning Assessment Scale. At the same time, subjective assessment of the patient performed with questionnaires and visual analogue scales showed less pronounced improvement in terms of depressive and anxiety symptoms, and high reduction of anhedonia. Some mild side effects of neurostimulation were observed, but they were transient and eliminated with stimulation parameters adjustment. This article discusses, despite response to the DBS treatment, difficulties and highlights the importance of the parallel use of different treatment options at one time and personalised therapy. Combined personality traits and past traumas require close attention of therapists and remains one of the most significant factors contributing to the development of treatment-resistant depression.